An Exploration Into Trust and Privacy Management in a Digital Age - Lin, Yue Jer (International Journal for Applied Information Management, 2022)
This study aims to inspect the effects of the privacy management and realize the relationship between use of trust and the quality of the privacy policy for the sites. This research applied four criteria of notice, access, choice and security that were identified by the FTC as Fair Information Practice to assess 476 websites for the trust and privacy management. Results indicated that approximately 36% of the websites used a trustmark, and that HiTrust/VeriSign was the most commonly used by businesses. The preferred trustmark varied by industry, such as sports sites preferring Verified by VISA, real estate sites preferring SOSA, telecommunication sites preferring HiTrust/VeriSign, and travel sites preferring TWCA. However, BBB Online and TRUSTe were displayed very hardly. The main findings showed that there were no obvious relationships between the use of trust marks and the notice criterion. On the contrary, there were very strong relationships between the use of trust marks and the access and choice criteria for all industries and overall.